How does surface mining impact surrounding miombo woodland bird communities? - Hickman, Rowan (Department of Biological Sciences, 2022)
Africa is estimated to contain almost one quarter of global biodiversity, but also a third of global non-fuel mineral resources. Together with relatively low past exploitation, this has led to a surge in mining investment and development over the past few decades. Mining negatively impacts biodiversity in numerous ways. One hotspot of mining activity in Africa is the Central African Copperbelt, which contains vast copper reserves and half of global minable cobalt. The Central African Copperbelt is located roughly in the centre of the miombo ecoregion, a biodiverse area that is listed as a global conservation priority, which provides ecosystem services that support over 100 million livelihoods. Despite its ecological and social importance, research on the impacts of mining and possible mitigation measures in the ecoregion is limited. This study was conducted in miombo woodlands inside and outside an ecological protection zone surrounding an open pit copper mine in north-western Zambia. It tested effect of distance from the mine, habitat structure and woodland protection on total avian species richness and the species richness of frugivores, granivores, insectivores, woodland and open habitat specialists, breeding and non-breeding species and Zambezian endemics. The results showed that distance from the mine and habitat structure did not significantly explain variation in total species richness or in the species richness of any of the ecological guilds tested. The most likely explanation for this is that mine effects on avian species richness are not detectable at the scale used in this study, implying that by the closest sampling sites (500m from the mines edge) the woodland had mitigated the mine's effects. This suggests that using woodlands as a barrier to mine pollution may be an effective form of mitigation. The results also showed that species richness of frugivores, insectivores, woodland habitat specialists, Zambezian endemic species and breeding species was not significantly explained by protection. However, total species richness and the species richness of granivores, open habitat specialists and non-breeding species all increased significantly outside of the ecological protection zone, which corresponded to woodland surrounded by cropland. These findings highlight the importance of unprotected woodland patches in the conservation of miombo bird species, since these may persist (likely in lower numbers) even in such fragmented patches within transformed habitats. Cropland expansion threatens woodland patches throughout the miombo ecoregion, and while protected areas are undeniably important in biodiversity conservation, matrix habitats may also potentially contribute to the maintenance of miombo species.